Engineering of the Filamentous Fungus Penicillium chrysogenum as Cell Factory for Natural Products - Guzmán-Chávez, Fernando; Zwahlen, Reto D.; Bovenberg, Roel A. L.; Driessen, Arnold J. M. (Frontiers in Microbiology, 2018)
Penicillium chrysogenum (renamed P. rubens) is the most studied member of a family of more than 350 Penicillium species that constitute the genus. Since the discovery of penicillin by Alexander Fleming, this filamentous fungus is used as a commercial -lactam antibiotic producer. For several decades, P. chrysogenum was subjected to a classical strain improvement (CSI) program to increase penicillin titers. This resulted in a massive increase in the penicillin production capacity, paralleled by the silencing of several other biosynthetic gene clusters (BGC), causing a reduction in the production of a broad range of BGC encoded natural products (NP). Several approaches have been used to restore the ability of the penicillin production strains to synthetize the NPs lost during the CSI. Here, we summarize various re-activation mechanisms of BGCs, and how interference with regulation can be used as a strategy to activate or silence BGCs in filamentous fungi. To further emphasize the versatility of P. chrysogenum as a fungal production platform for NPs with potential commercial value, protein engineering of biosynthetic enzymes is discussed as a tool to develop de novo BGC pathways for new NPs.